2020
DOI: 10.1364/oe.382139
|View full text |Cite
|
Sign up to set email alerts
|

Ultrabroadband light absorption based on photonic topological transitions in hyperbolic metamaterials

Abstract: Photonic topological transitions (PTTs) in metamaterials open up a novel approach to design a variety of high-performance optical devices and provide a flexible platform for manipulating light-matter interactions at nanoscale. Here, we present a wideband spectral-selective solar absorber based on multilayered hyperbolic metamaterial (HMM). Absorptivity of higher than 90% at normal incidence is supported over a wide wavelength range from 300 to 2215 nm, due to the topological change in the isofrequency surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…When the IFC of structure transitions between open hyperboloid and closed ellipsoid, PTT point will exist. The regime, which is very close to PTT point, is also known as the epsilon-near-zero (ENZ) regime [ 21 ]. At PTT point, HMMs can significantly suppress the diffraction and scattering of incident light, which can provide a new way for efficiently manipulating light-matter interactions at nanoscales.…”
Section: Design and Theoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…When the IFC of structure transitions between open hyperboloid and closed ellipsoid, PTT point will exist. The regime, which is very close to PTT point, is also known as the epsilon-near-zero (ENZ) regime [ 21 ]. At PTT point, HMMs can significantly suppress the diffraction and scattering of incident light, which can provide a new way for efficiently manipulating light-matter interactions at nanoscales.…”
Section: Design and Theoriesmentioning
confidence: 99%
“…In contrast to the closed iso-frequency contour (IFC) of traditional materials, the hyperbolic IFC is open and large wave-vectors can be supported in HMMs [ 15 ]. This special feature has been explored for many prospective applications in hyperlens [ 6 ], spontaneous emission enhancement [ 16 , 17 ], Goos–Hänchen effect [ 18 , 19 ], photonic topological transition [ 20 , 21 , 22 , 23 , 24 ], photonic spin hall effect [ 25 , 26 ], and Casimir force [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since Landy et al demonstrated the first metamaterial absorber with one perfect absorption peak in the microwave band through an experiment 19 , the control and engineering of the spectral absorption properties of MPAs has attracted significant interest. In their experiment, broadband perfect absorption was achieved with MPAs in microwave regime [20][21][22][23][24] and was extended from visible [25][26][27][28][29][30][31][32][33][34][35][36][37] , infrared [38][39][40][41][42][43][44][45][46][47][48][49][50][51] and THz [52][53][54][55][56][57] bands. This study will compare these representative theoretical and experimental works on the topic of broadband MPAs from visible to infrared bands in supplement document.…”
Section: Introductionmentioning
confidence: 98%
“…These possess opposite signs for the parallel and perpendicular components of effective permittivity. Varieties of HMMs have been reported in the literature operating in the terahertz (THz) and optical regimes [4], [5] for potential applications in super resolution imaging [1], [6], filtering [7], [8], extreme polarization anisotropy of photoluminescence [9], energy harvesting [10], biosensors [11], [12], and absorbers [10], [13]- [15].…”
Section: Introductionmentioning
confidence: 99%